Stoetzer, Bettina 2022. Ruderal City: Ecologies of Migration, Race, and Urban Nature in Berlin. - Eeva Berglund (Suomen Antropologi, 2024)
Stoetzer, Bettina. Ruderal City: Ecologies of Migration, Race, and Urban Nature in Berlin. Duke University Press Books. 2022. 243 p. Part of the book series, Experimental Futures: Technological Lives, Scientific Arts, Anthropological Voices, edited by Michael M. J. Fischer and Joseph Dumit. ISBN 10: 1478018607 (softcover) ISBN 13: 9781478018605 (hardcover).